The Impact of Global Economic Crisis Phenomena on Migration Processes through the Relationship between Consumption and Saving - Tukhtarova, Evgeniya Kh. (Economy of Regions, 2020)
The paper studies how the global crisis influences migration processes that are accompanied by structural changes in the relationship between consumption and saving of the population of different countries. The article examines the hypothesis on the multidimensionality of the impact of the crisis on the population of various countries. To solve the research problems, analytical, statistical and econometric methods were applied. A combination of these methods allowed identifying structural shifts in the relationship between consumption and saving because of changes in technological paradigms. Consequently, such shifts lead to changes in the welfare of the population of different countries. While for some countries these changes will be acute, negative, and short-term, for others this process will be less acute, but with long-term negative consequences. At the same time, contrary to the examined economic crises of the XVIII-XX centuries that demonstrated a decrease in migration, in the XXI century, new crisis phenomena show the absence of such a connection. The author’s position confirms the findings of other researchers stating that migration processes are loosely connected to short-term economic crises in the host territory. However, the close link be- tween migration flows and long-term development factors of the host territory indicates a high potential of the country in a crisis. The conducted study has confirmed this hypothesis. The obtained results can be used to justify propos- als and measures for regulating migration processes, taking into account the priority of national interests for the scientific, technological and economic development of the Russian Federation.